EVALUATION OF DRUG MANAGEMENT IN SALAMAN 1 PRIMARY HEALTH CENTER MAGELANG DURING THE COVID 19 PANDEMIC - Endaryanti Wulandari; Aris Widayati (Universitas Muhammadiyah Magelang, 2021)
The scope of drug management in Primary Health Center (PHC) includes planning/selection, procurement, storage, distribution, control of use, and documentation and reporting. During the COVID-19 pandemic, there were many changes in regulation and management in Primary Health Center. Such a situation certainly has an impact on the drug management of Primary Health Center. The purpose of this study is to evaluate drug management in Salaman 1 Primary Health Center in Magelang District, Central Java Province, during the COVID-19 pandemic in 2020. This research is an evaluative study using a descriptive design with a qualitative approach. The data was obtained by three methods, i.e., direct observation, interview, and secondary data. Direct observation was applied to observe the medicines' storage space. Interviews were conducted with five informants selected purposively according to the research's purpose. The assessments of secondary data were performed from the available and relevant data documentations. Data were analyzed by triangulation approach of the three types of data produced, namely observation data, interview data, and secondary data assessment. The results show several problems regarding drug management in Salaman 1 PHC during the COVID-19 pandemic. The drug selection is not precisely suitable for the needs, while drug procurement cannot always be arranged according to the planning. Furthermore, drug distribution is relatively impeded. Control of use found the number of expired and almost expired drugs increases. Drug storage and documentation are the two steps in the drug management cycle conducted appropriately in Salaman 1 PHC during the COVID-19 pandemic. This evaluative study concludes that the COVID-19 pandemic affected the drug management cycle in Salaman 1 PHC in Magelang District in 2020. Therefore, coordination among stakeholders must be improved to anticipate unforeseen circumstances, especially during the pandemic situation. The impacts of new policy implementations must be anticipated by testing, monitoring, and evaluating.